Post-harvest behavior of green peppers after pectin methyl esterase and calcium chloride application - Paixão, Airles Regina da Costa (Emirates Journal of Food and Agriculture, 2020)
The green pepper (Capsicum annuum L.) is an important Brazilian vegetable and it is very much appreciated, besides being a source of vitamins, minerals and fibers. However, it has serious post-harvest shelf-life problems, such as tissue softening. The exogenous application of pectin methyl esterase and calcium has been shown to be efficient in maintaining the firmness of several fruits. Thus, the present study had as objective to evaluate the effects of the application of exogenous pectin methyl esterase (PME) and calcium in post-harvest conservation of the cv. Yolo Wander. For this, the green peppers were submitted to vacuum infusion with water, vacuum infusion with 7% of calcium chloride and vacuum infusion of PME associated to 7% calcium chloride, fruits without infusion were used as control. Loss of fresh mass, fruit firmness, peel color, soluble solids content, pH, total acidity and PME activity were evaluated. In relation to the loss of fresh mass there was a significant increase over time in all treatments. Also, according to the results, the fruits not immersed or those immersed in calcium chloride showed greater maintenance of the firmness, as well as smaller variations in the activity of the SME and low levels of organic acids. The vacuum infusion with 7% calcium chloride maintained the firmness and the physicochemical characteristics of the green pepper. However, the application of PME + CaCl2 did not promote the maintaining desirable firmness characteristics for the green pepper.